Student Perception on Enhancing Learning Motivation via Guest Lectures in the English Language Education Department - Danan Darajat; I Putu Suyasa Ariputra (International Journal of Instructions and Language Studies, 2024)
The growing intricacy of cognitive processes as learning advances underscores the need of fostering human capacity through education. However, educational interventions, particularly in the realms of emotions and spirituality, have yet to reach their ideal level, particularly within the framework of online learning. The reliance on technology, namely the existence of GPT Chat, has diminished students' incentive to learn, thus necessitating the use of alternative approaches like as guest lectures to bring fresh viewpoints and enhance self-driven learning motivation. The study investigates student perspectives on enhancing learning motivation through guest lectures in the Department of English Language Education. The objective is to offer fresh perspectives on enhancing the caliber of education in the major. The analysis process utilizes Keller's ASCR technique. Data gathering strategies encompass the distribution of surveys subsequent to guest lectures, employing modified questions derived from prior research. Research findings indicate that instructors have a significant impact on cultivating students' focus, connection, and self-assurance. The students expressed contentment with the guest lectures and anticipated a higher frequency of similar activities. In summary, this study demonstrates that students hold a favorable view of initiatives aimed at enhancing learning motivation through guest lectures at the Department of English Language Education.